- #1

chwala

Gold Member

- 2,727

- 382

## Homework Statement

given## dm/dt=120(t-3)^2## find m(t)[/B]## Homework Equations

## The Attempt at a Solution

now i have a problem here the first attempt ## ∫120(t-3)^2dt ##

= ##120∫(t^2-6t+9)dt##

=## 120(t^3/3-3t^2+9t)+k ##

but if you use chain rule you have

## ∫120(t-3)^2dt ## let ## u = t-3 ##then it follows that ##du=dt## thus we have

##∫120u^2du## =##(120u^3)/3 + k ##=##(120(t-3)^3)/3 ## this second solution clearly is the correct answer having four terms + a constant, why is the first solution wrong ? its having three terms + a constant?[/B]